ChemInform Abstract: Crystal Structure Relation Between Tetragonal and Orthorhombic CsAlD4: DFT and Time‐of‐Flight Neutron Powder Diffraction Studies. Issue 5 (January 2016) - Bernert, Thomas; Krech, Daniel; Kockelmann, Winfried; Felderhoff, Michael; Frankcombe, Terry J.; Weidenthaler, Claudia
Abstract: The deuterium positions of orthorhombic and tetragonal CsAlD4 are predicted by DFT calculations and refined from time‐of‐flight neutron powder diffraction data.